Malignant melanoma of the oral cavity. Review of the literature and experience in a Peruvian Population - Guevara-Canales, Janet-Ofelia (2012)
Objective: To determine the epidemiological profile of malignant melanoma cases treated at the National Institute for Neoplastic Diseases "Dr. Eduardo Caceres Graziani" (INEN) over the period 1952 to 2008. Study design: All clinical records with complete data of patients presenting a histopathological diagnosis of malignant melanoma of the oral cavity were reviewed. Data such as age, gender, location, tumor size, disease length, presence of metastasis, treatment received and year of admission were recorded. Results: During the study period 97 cases were found. The average age of patients was 52.85±1.6 years old mostly between 50 and 59 years old; the predominant gender was the female. The most common location was the palate and there was 58.8% of cases with a tumor size bigger than or equal to 4 cm. The length of the disease in 38.1% of the cases was longer than a year and in great part of the cases (69.1%) there was no metastasis. The treatment of choice was the surgery plus radiotherapy in 38.1% of the cases. According to the admission date it was also noted that the number of cases is increasing. Conclusion: The results of this study demonstrate a late diagnosis and an increasing frequency of this neoplasia in the oral cavity.